2022
DOI: 10.1002/aocs.12573
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic hydrolysis and fermentation of soy flour to produce ethanol and soy protein concentrate with increased polyphenols

Abstract: There is a need to effectively concentrate soy protein from defatted soy flour (DSF) while simultaneously valorizing the carbohydrate-rich byproduct, which would otherwise be a waste. This study aims to evaluate a process developed to produce soy protein concentrates (SPC) by substantially hydrolyzing carbohydrates from DSF with the help of enzymes into water-soluble saccharides and monomeric sugars, which were simultaneously utilized by Saccharomyces cerevisiae for fermentation into ethanol. The enzyme mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
(57 reference statements)
1
0
0
Order By: Relevance
“…Therefore, the increased antioxidant activity in hydrolysates could be attributed to the enzymatic release of phenolic compounds from the lentil hull food matrix. Moreover, the antioxidant increase could be attributed to the release of oligosaccharides, as previously reported for pectin oligosaccharides [ 35 ]. Comparisons among the enzymatic treatments indicated that Ultraflo ® XL, Ultimase ® BWL 40, Viscozyme ® L and Pectinex ® Ultra Tropical produced lentil hull hydrolysates with a higher antioxidant activity as compared to Ultraflo ® Max, Celluclast ® and Shearzyme ® Plus 2X ( p ≤ 0.05).…”
Section: Resultssupporting
confidence: 66%
“…Therefore, the increased antioxidant activity in hydrolysates could be attributed to the enzymatic release of phenolic compounds from the lentil hull food matrix. Moreover, the antioxidant increase could be attributed to the release of oligosaccharides, as previously reported for pectin oligosaccharides [ 35 ]. Comparisons among the enzymatic treatments indicated that Ultraflo ® XL, Ultimase ® BWL 40, Viscozyme ® L and Pectinex ® Ultra Tropical produced lentil hull hydrolysates with a higher antioxidant activity as compared to Ultraflo ® Max, Celluclast ® and Shearzyme ® Plus 2X ( p ≤ 0.05).…”
Section: Resultssupporting
confidence: 66%